Our Lady of Fátima and Marian Myth in portuguese cinema - Cunha, Paulo (2014)
The Marian myth and Our Lady of Fatima are part of a long tradition in Portuguese society. They form a collective unconscious that belongs to Portuguese culture from the intense fights of the First Portuguese Republic, through the New State dictatorship until the Democratic regime instated on 25 April l974. As a consequence, Portuguese cinema also portrays, throughout its history, the apparitions of the Virgin Mary, known in Portugal since the late 1920s as Our Lady of Fatima. It is the purpose of our study to analyze how the apparitions and Our Lady of Fatima appear in Portuguese national cinema and the way it portrays the Marian myth.